IMPACT OF UKRAINE’S FOREIGN ECONOMIC ACTIVITY ON THE EU ENERGY MARKET (World of finance, 2024)
Introduction. Increasing energy self-sufficiency and ensuring sustainable development are important tasks for countries in the modern world. For Ukraine, which has a significant potential in energy production, foreign economic activity on the energy market of the European Union becomes a strategic aspect in the management of energy resources. In the conditions of modern geopolitical instability and the emphasis on the transition to renewable energy sources, the interaction of Ukraine and the European Union on the energy market is of particular importance. Thanks to its geographical location and developed energy infrastructure, Ukraine can become an important player in ensuring energy security for the EU. However, on its way to European integration, Ukraine has both beneficial aspects of cooperation and possible challenges that will need to be resolved in order to achieve effective geopolitical cooperation between Ukraine and the European Union.The purpose of the article is to analyse Ukraine’s foreign economic activity on the EU energy market, its impact on the transformation of the EU energy market, to research the process of Ukraine’s integration into the EU energy network, to outline the proposals for improving Ukraine’s competitive position in the EU energy system.Results. The impact of Ukraine’s foreign economic activity on the energy market of the European Union was studied, the process of integration of the Ukrainian electricity network into the EU’s Energy System was considered, the experience of import-export operations between Ukraine and EU countries was analyzed, problems and possible challenges in the process of electricity networks synchronization were outlined, and possible solutions to the problems were proposed for conducting more effective foreign economic activity.Prospects. The subject of further research is the improvement of Ukraine’s integration into the EU Energy Network, the research of the possible implementation of green energy taking into account the requirements of the European Green Deal on decarbonization and greening of the EU energy sector.